PERKIRAAN DAMPAK BENCANA TSUNAMI TERHADAP KERUGIAN EKONOMI DI KABUPATEN PESISIR SELATAN - Asharafi, Fithratul; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
The tsunami is a catastrophe that leaves a large number of victims and economic damages, particularly in coastal regions like West Sumatra Province's Pesisir Selatan Regency. The government needs research on predicted economic damages and losses as a reference when developing policies to stop pre- and post-tsunami disasters. The Pesisir Selatan Regency tsunami disaster's anticipated effects in this study are based on BNPB Regulation No. 4 of 2012, which calls for an 11-meter sea level rise away from the coast. analysis The area affected by the tsunami was identified using the cost-distance method. The impacted area of agricultural land and plantations serves as the damage indicator. According to the results of the estimated impact of the 11-meter tsunami, the impacted area is 9,970.92 ha, 2,278.69 ha of it is affected by agriculture, and 4,870.7 ha of it is damaged by plantations. Rp. 95.412.280.674 in economic losses have been suffered by agricultural land, Rp. 1.586.436.733 by cocoa plantations, Rp. 13.595.505.700 by rubber plantations, and Rp. 26.073.748.800 by oil palm plantations.